RANCANGAN UNDANG-UNDANG PEMBANTU RUMAH TANGGA SEBAGAI SUATU HASIL IMPLEMENTASI ADVOKASI DALAM UPAYA PERLINDUNGAN HUKUM TERHADAP PEMBANTU RUMAH TANGGA - Soraya, Joice (JURNAL KONSTITUSI, 2011)
Housemaid (PRT) in Indonesia represent law phenomenon, which till now still fought to be poured in a law, and regulation utilize to give protection of law for them. Existence of labor law and employee in this time by substantial still oriented and limited gone into effect to laboring labor in formal sector while practical housemaid do not touch guarantee protection of law at all. Though the condition of housemaid also have ugly standard in distorting area, guarantee of social and protection of law. Resistance and avocado to housemaid then conducted more intensive, organize and is systematical, after passing step of avocado decanted in a draft of law which now there are in Parliament board to is immediately specified to become a code form, what can become umbrella punish to housemaid in Indonesia.Â